INTERPROFESSIONAL COLLABORATION IMPROVING THE QUALITY OF HEALTH MOTHER AND CHILD ON EXTENSION WILL THE ROLE OF ULTRASOUND EXAMINATION (USG) PREGNANCY - Sri Mulyati; Muhammad Irwan Katili; Emi Murniati (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2016)
Interprofessional Collaboration program is Community Service Health Polytechnic Semarang organized by collaboration between the Department /Major environment in Ministry of Health Polytechnic of Semarang. Indonesian society in order to achieve a healthy and prosperous required equitable national development efforts in all aspects of life including health.. Data 2014 of the Health Profile Semarang City Health Office showed the prevalence of maternal and infant mortality in the Region Health Center Bangetayu Genuk District of Semarang. Therefore, there should be collaborative efforts between the Department in order to take part in activities carried out in an integrated and sustainable. Thus, the Ministry of Health Polytechnic Semarang gait may be integrated through interprofessional collaboration activities to help solve health problems, especially in the area of urban village Puskesmas Bangetayu ie Bangetayu wetan Genuk districts of Semarang. With these activities, the public is expected to know the role of ultrasound examination and determine the usefulness of ultrasound examination, benefit of ultrasound examination in pregnancy (antenatal care) in efforts to reduce maternal and infant mortality. Ultrasound examination can be performed by medical indications to get the full data will be the condition of the fetus in the mother's womb. Usually done 3-4 times during pregnancy.